Virtuous people and evil elites? The role of moralizing frames and normative distinctions in identifying populist discourse - Sophia Hunger (Political Research Exchange, 2024)
Populism has been a much-studied concept in Social Science research. A great share of research on the concept has been dedicated to measuring the occurrence of populism in political text. In this article, I propose a novel measure of populism that considers established theoretical assumptions, i.e. presenting the people as morally superior and the elite as evil. This moral framing of the antagonistic groups is necessary to identify populist discourse while keeping it separate from empirically related concepts, e.g. radical right-wing ideology. The novel two-step dictionary detects morally-framed references to both groups. I apply this approach to a text corpus of all speeches given in the European Parliament from 1999 to 2014 and carry out extensive validity checks. Taking the moralizing notion of populism more seriously not only contributes to our theoretical understanding of populist discourse and its impact on the political sphere, but the new measure also improves previous approaches to measuring populism.
https://doi.org/10.7910/DVN/9UGJVM
Keywords: 320; Populism; parties; European parliament; text-as-data; moralization